Maternal and perinatal outcome in antepartum haemorrhage patients attending tertiary care hospital in central India: a prospective observational study - Anjankar, Priyanka S.; Ramteke, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Antepartum haemorrhage (APH) is an emergency obstetrical condition that accounts for 2-5% of pregnancies and contributes to high level of maternal and perinatal mortality and morbidity. The present study was undertaken to assess the incidence of APH and to determine the maternal and fetal outcome in women with APH. Methods: This study was conducted in 130 women diagnosed with APH (gestational age ≥28 weeks) admitted in the department of obstetrics and gynaecology, at tertiary care hospital in central India over a period of 18 months from January 2020 to June 2021. Results: The overall incidence of APH was 1.09% and majority of them had abruptio placentae (AP-53.08%) followed by placenta praevia (PP-38.46%) and unknown (UK-8.46%). Anaemia (90%) was the commonest maternal morbidity. A significant association found between APH type and HELLP infection (p<0.0001), PPH (p=0.028) and DIC (p<0.0001). Rate of maternal morality was 9.23% and commonest causes of mortality were renal failure and PPH (91.67% each). Most common neonatal morbidities were birth weight of <2.5 kgs (84.32%) and NICU admission (27.61%). APH type was significantly associated with birth weight (p<0.0001). Majority of neonates were born live (56.72%), 36.57% were IUDs, 6.72% were still born, and 14.18% were neonatal deaths. APH type was significantly associated with live births and IUDs, (p<0.0001). Conclusions: APH is still a leading cause of maternal morbidity and mortality. Most of the patients were booked at other centres and were presented late with complications at the time of admission. Both these factors have contributed significantly to the incidence of APH as well as maternal and perinatal morbidity and mortality.